Chemistry of polyhalogenated nitrobutadienes, 10: Synthesis of highly functionalized heterocycles with a rigid 6-amino-3-azabicyclo[3.1.0]hexane moiety - Zapol’skii, Viktor A.; Namyslo, Jan C.; de Meijere, Armin; Kaufmann, Dieter E. (Beilstein Journal of Organic Chemistry, 2012)
The nitropolychlorobutadienes 3, 4 are valuable building blocks for various amination and successive heterocyclization products. Nucleophilic substitution reactions of the partially protected, bioactive amines 1, 2 with either vinyl, imidoyl or carbonyl chlorides result in the formation of the enamines 11, 12, 13, 16, 25, the amidine 6, and the amides 20, 21, respectively. In the following, cyclization to the highly functionalized pyrazoles 27, 28, pyrimidine 26 and pyridopyrimidine 24 succeeded. Deprotection of 21, 12 and 28 proved to be only partially feasible.
Keywords: isothiazole; nitrochlorobutadiene; nitropyrazole; nucleophilic substitution; pyrimidine; small rings